Effect of gas flow rate on oxidation behaviour of alloy 625 in wet air in the temperature range 900–1000 °C. Issue 2 (13th July 2016) - Huczkowski, P.; Lehnert, W.; Angermann, H.‐H.; Chyrkin, A.; Pillai, R.; Grüner, D.; Hejrani, E.; Quadakkers, W. J.
Abstract : In many industrial processes, the flow rate of hot gaseous service environments may be in the range of several m/s. In the present paper, the effect of gas flow rate on the high temperature oxidation behaviour of alloy 625 in wet air is presented. The gas velocity was varied from near static conditions to linear gas flow rates up to 6 m/s. The oxidation kinetics were studied by gravimetry during cyclic/discontinuous testing at 900 and 1000 °C. The oxide scales and the subsurface depletion zones formed during exposure were studied by light optical microscopy, scanning electron microscopy with energy dispersive X‐ray analysis and, for selected specimens, by electron backscatter diffraction. It was found that Cr loss due to formation of volatile species is substantially enhanced by high gas flow rates thus significantly influencing the oxidation limited life time of the oxidising component. Within the studied range of flow rates no plateau value was reached, the Cr loss being substantially larger at a flow of 6 m/s than at 0.7 m/s. Additionally, it was found that geometrical factors of the test specimen substantially affected the extent of volatile species formation. Especially the leading edge of the specimen exhibited more extensive Cr loss than the other specimen areas. Abstract : During exposure of alloy 625 in wet air at 900–1000 °C chromium loss due to formation of volatile Cr species increases with increasing gas flow rate up to the maximum considered value of 6 m/s. Geometrical factors of the test specimen substantially affected the extent of volatile species formation; especially the specimen leading edge exhibited more extensive formation of volatile Cr species than other specimen areas.